Parents of Children With Disabilities: Telling a Different Story - Goddard, Jay A.; Lehr, Ron; Lapadat, Judith C. (Canadian Journal of Counselling and Psychotherapy, 2007)
This study explored a deconstructed view of disability with parents of children with disabilities. We analyzed stories collected in open-ended focus groups using criteria derived from constructivist principles of narrative therapy. A thematic analysis, grounded in a critical constructivist perspective, yielded four thematic categories: stories about other people's assumptions, stories about dealing with difference, stories about professionals, and stories about disability. These parents' narratives define and deconstruct the dominant discourse about being the parent of a child with disabilities and reveal insights about the impact of stereotypic views of disability. Implications for counselling parents in ways that honour their insights are discussed.